2019
DOI: 10.1038/s12276-019-0278-3
|View full text |Cite|
|
Sign up to set email alerts
|

Inhibition of RIPK1-dependent regulated acinar cell necrosis provides protection against acute pancreatitis via the RIPK1/NF-κB/AQP8 pathway

Abstract: Currently, preliminary results have confirmed the existence of receptor-interacting protein kinase 3 (RIPK3) and mixed lineage kinase domain-like protein (MLKL)-dependent necroptosis of pancreatic acinar cells during early acute pancreatitis (AP), which might be a potential target for the effective regulation of necroinflammatory injury. However, the exact effect of receptor-interacting protein kinase 1 (RIPK1)-dependent regulated acinar cell necrosis on AP is still uncertain. In our study, we first explored t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 51 publications
0
26
0
Order By: Relevance
“…In fact, Nec-1 is indeed associated with systemic inflammation. In the rat model of acute pancreatitis, rats treated with Nec-1 displayed significant milder symptoms and pathophysiological characteristics, and Nec-1 alleviated the extent of systemic inflammatory response caused by acute pancreatitis, the underlying mechanism of this protective effect is probably related to RIP1/NF-κB p65/AQP8 axis [ 195 ]. Although there is no research directly showing the relation between necroptosis and COVID-19, or the effect of Nec-1 in COVID-19, the strong anti-inflammation ability of Nec-1 makes us predict that Nec-1/Nec-1 analogues might have the capability to alleviate cytokine storm, systemic inflammation and thus COVID-19.…”
Section: Nec-1 and Covid-19mentioning
confidence: 99%
“…In fact, Nec-1 is indeed associated with systemic inflammation. In the rat model of acute pancreatitis, rats treated with Nec-1 displayed significant milder symptoms and pathophysiological characteristics, and Nec-1 alleviated the extent of systemic inflammatory response caused by acute pancreatitis, the underlying mechanism of this protective effect is probably related to RIP1/NF-κB p65/AQP8 axis [ 195 ]. Although there is no research directly showing the relation between necroptosis and COVID-19, or the effect of Nec-1 in COVID-19, the strong anti-inflammation ability of Nec-1 makes us predict that Nec-1/Nec-1 analogues might have the capability to alleviate cytokine storm, systemic inflammation and thus COVID-19.…”
Section: Nec-1 and Covid-19mentioning
confidence: 99%
“…Regarding the contribution of necroptosis to the pathophysiology of AP, it is unclear whether inhibition of necroptosis mediated by RIPK3/MLKL is effective in protecting against pancreatic damage because different outcomes have been reported. Inhibition of necroptosis with the RIPK1 inhibitor necrostatin-1 or by genetic deletion of either Ripk3 or Mlkl provides protection against AP by reducing acinar cell vacuolization and necrosis 15 19 . In contrast, necrotizing pancreatitis is accelerated in Ripk3 -deficient mice 20 .…”
Section: Introductionmentioning
confidence: 99%
“…However, NF-κB inhibition in IBS model rats did not fully restore the intestinal epithelium ( 13 ). Furthermore, Duan et al ( 31 ) found that the early acute receptor-interacting protein kinase 1 (RIPK1)/NF-κB/AQP8 axis mediated the RIPK1-dependent acinar cell necrosis. Consistent with this, the present study suggested that the NF-κB-mediated regulation of AQP8 expression was likely to be involved in ethanol-induced IEB dysfunction.…”
Section: Discussionmentioning
confidence: 99%